Pengaruh Variasi Produk Terhadap Keputusan Pembelian Pada Aplikasi Grab di Kota Bima - M. Syahrul Alamsyah; Ita Purnama; Nur Khusnul Hamidah (Journal of Mandalika Literature, 2024)
(1)To determine whether there is a significant influence using a partial test between product variations on purchasing decisions on the Grab application in the city of Bima,(2) This type of research is associative, the instrument in this research is using a questionnaire with a Likert scale, the population is all consumers who have used or made purchases using the Grab application in the city of Bima, the number of which cannot be known (unkown population) which is the sample in the research There are 96 of them using a purposive sampling technique, data collection techniques, namely through observation, questionnaires and literature study with data analysis techniques, namely: validity test, reliability test, simple linear regression, coefficient of determination, simple correlation coefficient and t test. (3) The results of this research are that product variations have a significant effect on purchasing decisions on the Grab application in the city of Bima.